Contrast-Induced Nephropathy Factors and Prevalence in Patients Getting Multi-Vessel Percutaneous Coronary Intervention - Bakht Umar Khan, Fahad Khalid, Omer Aziz Mirza, Fayaz Ahmed Memon, Muhammad Shahid, Muhammad Shehram (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the prevalence of contrast-induced nephropathy and its associated risk factors in patients undergoing multi-vessel percutaneous coronary intervention (PCI). Study Design: Observational/ Prospective study Place and Duration: Armed forces institute of cardiology & National Institute of heart diseases, Rawalpindi, during from the period September 2019 to Feb 2020. Methods: There were 112 patients of both genders with ages 18-75 years were presented in this study. Data on enrolled patients’ age, gender, BMI, marital status and education level were collected after receiving written permission from each patient. This research included people who had undergone a percutaneous coronary intervention. Serum creatinine >0.5mg/dl from the baseline value was classified as contrast induced nephropathy. CIN-related risk factors were studied. Data was analyzed using SPSS 24.0. Results: The mean age of the patients was 51.6±9.53 years and had mean BMI 23.5±15.67 kg/m2. Majority were males 68 (60.7%) and 44 (39.3%) were females. There were 75 (66.96%) patients married and 55 (49.1%) patients were educated. Frequency of contrast induced nephropathy was among 25 (22.3%) cases. Most common risk factor of CIP was contrast volume 19 (76%) and hypertension found in 17 (68%) cases, followed by diabetes mellitus in 15 (60%) cases, age >65 years in 13 (52%) cases, CHF in 11 (44%) cases, smoking history in 9 (36%) cases and family history of CAD was 4 (16%). Conclusion: Patients undergoing PCI are at a considerable risk of developing contrast-induced nephropathy. Among the risk variables for CIN were anaemia (age >70 years), diabetes mellitus (contrast volume >150 ml), and heart failure. Keywords: Risk Factors, Contrast Induced Nephropathy, Percutaneous Coronary Intervention